Drug-induced Skin Lesions in Cynomolgus Macaques Treated with Metabotropic Glutamate Receptor 5 (mGluR5) Negative Allosteric Modulators. (October 2015) - Palanisamy, Gopinath S.; Marcek, John M.; Cappon, Gregg D.; Whritenour, Jessica; Shaffer, Christopher L.; Brady, Joseph T.; Houle, Christopher
Three orally administered metabotropic glutamate receptor 5 (mGluR5) negative allosteric modulators caused skin lesions consistent with delayed type-IV hypersensitivity in cynomolgus macaques in 2- and 12-week toxicity studies. Several monkeys developed macroscopic skin lesions in multiple locations after 8 to 9 days of dosing; the most prominent effects involved the genital region of males and generalized erythema occurred in both sexes. Microscopic lesions occurred in both clinically affected and unaffected areas and were characterized by lymphocytic interface inflammation, subepidermal bullae, and individual keratinocyte vacuolation/necrosis. In the 12-week study, clinical effects in 2 animals resolved with continued dosing, whereas in others the inflammatory process progressed with 1 female exhibiting systemic lymphocytic inflammation in multiple tissues. The inflammatory infiltrate consisted of CD3 and CD4 positive T lymphocytes with minimal CD68 positive macrophages and only rare CD8 positive T lymphocytes. A subset of animals given a dosing holiday was subsequently rechallenged with similar lesions developing but with a more rapid clinical onset. These skin lesions were consistent with type-IV delayed hypersensitivity with some features comparable to bullous drug eruptions in humans. A relationship between these findings and the intended mode of action for these compounds could not be ruled out, given the occurrence across different chemotypes.